Sotorasib-impaired degradation of NEU1 contributes to cardiac injury by inhibiting AKT signaling - Mengting Cheng; Wentong Wu; Qing Li; Xinyu Tao; Feng Jiang; Jinjin Li; Nonger Shen; Fei Wang; Peihua Luo; Qiaojun He; Ping huang; Zhifei Xu; et al. (Cell Death Discovery)
Abstract Sotorasib, the inaugural targeted inhibitor sanctioned for the management of patients afflicted with locally advanced or metastatic non-small cell lung cancer presenting the KRAS G12C mutation, has encountered clinical application constraints due to its potential for cardiac injury as evidenced by safety trials. This investigation has elucidated that the heightened expression of neuraminidase-1 (NEU1) constitutes the principal etiology of cardiac damage induced by sotorasib. Mechanistically, sotorasib treatment inhibited the ubiquitinated degradation of NEU1, leading to its elevated expression, which induced downstream AKT signaling pathway inhibition and mitochondrial dysfunction leading to cardiomyocyte apoptosis. Meanwhile, in vivo and in vitro studies showed that D-pantothenic acid (D-PAC) alleviated sotorasib-induced cardiac damage by promoting NEU1 degradation. In conclusion, this study revealed that NEU1 is a key protein in sotorasib cardiotoxicity and that reducing the level of this protein is a critical strategy for the clinical treatment of sotorasib-induced cardiac injury. Schematic representation of a mechanism.